A Case Study of Maintenance Management Systems in Malaysian Complex and High-rise Industrialized Building System Buildings - Ismail, Zul-Atfi; Mutalib, Azrul A.; Hamzah, Noraini (International Journal of Economics and Financial Issues, 2016)
The implementation of a maintenance management system faced many issues due to defect repetition and lack of proper structure management planning. A case study was undertaken among complex and high-rise Industrialised Building System (IBS) buildings in Malaysia to identify a key of problem areas and to establish elements of good practice. The study evaluated the performance of the existing maintenance management system used by complex and high-rise IBS buildings to determine whether there is a need to improve current maintenance management system. Results showed that existing performance is far below best practice standards and that the use of emerging technology such as Building Information Modelling (BIM) is very limited. This led to the development of a key feature of the maintenance management system using emerging technology to assist engineers at complex and high-rise IBS buildings to improve their existing approaches to maintenance management. Keywords: Maintenance management; process; Malaysia; IBS buildings; BIM JEL Classifications: O1; O2; O4